The inhabitant [videorecording (DVD)] - Bachar, Kevin; A'zion, Odessa; Bibb, Leslie; Mulroney, Dermot (Gravitas Ventures, 2022)
High school can be a nightmare for any teenager. But Tara lives in the shadow of a harrowing family curse, she's a descendant of ax-murderess Lizzie Borden. As Tara begins to hear voices and have paranoid visions of butchering her family, people in her small town are attacked and killed, and all evidence points to her. Gripped by her family's past, Tara must confront the demons that possess her, both real and imaginary, and a shocking truth in this chilling psychological horror ride.